Muscle-specific increased expression of JAG1 improves the skeletal muscle phenotype in dystrophin-deficient mice - Felipe de Souza Leite; Matthias R. Lambert; Tracy Yuanfan Zhang; James R. Conner; Joao A. Paulo; Sheldon Furtado Oliveira; Sanjukta Guha Thakurta; Jennifer Bowles; Emanuela Gussoni; Steven P. Gygi; Jeffrey J. Widrick; Louis M. Kunkel (Proceedings of the National Academy of Sciences, 2025)
Therapeutic strategies for Duchenne muscular dystrophy (DMD) will likely require complementary approaches. One possibility is to explore genetic modifiers that improve muscle regeneration and function. The beneficial effects of the overexpression of Jagged-1 were described in escaper golden retriever muscular dystrophy (GRMD) dogs that had a near-normal life and validated in dystrophin-deficient zebrafish. To clarify the underlying biology of JAG1 overexpression in dystrophic muscles, we generated a transgenic mouse (mdx 5cv - JAG1 ) model that lacks dystrophin and overexpresses human JAG1 in striated muscles. Skeletal muscles from mdx 5cv - JAG1 and mdx 5cv mice were studied at 1-, 4-, and 12-mo time points. JAG1 expression in mdx 5cv - JAG1 increased by 3 to 5 times compared to mdx 5cv . Consequently, mdx 5cv - JAG1 muscles were significantly bigger and stronger than dystrophic controls, along with an increased number of myofibers. Proteomics data show increased dysferlin in mdx 5cv - JAG1 muscles and an association of the histone methyltransferase Nsd1 with the phenotype. Our data support the positive effect of JAG1 overexpression in dystrophic muscles.